PERAN KOMUNIKASI ANTARPRIBADI DAN KOMUNIKASI ORGANISASI DALAM MENJAGA TRADISI RUWAT BUMI DI DESA KARANGSARI, KECAMATAN KARANGANYAR, KABUPATEN PEKALONGAN - Azzam Nabil Hibrizi; Syafika Saffanah (Universitas Baturaja, 2023)
This research discusses the role of interpersonal communication in maintaining the Ruwat Bumi tradition in Karangsari Village, Karanganyar, Pekalongan. Nowadays, local culture can be eroded by incoming foreign cultures. So, a strong effort is needed to maintain the local culture. The presence of interpersonal communication is able to maintain culture. Interpersonal communication itself has the meaning of communication that can be done between individuals without meeting directly. There are three main stages of effort, namely knowledge, planning, and creativity. Researchers use qualitative methods with data collection in the form of interviews and observations (observation). Primary data was obtained from interviews. While secondary data is obtained from books and scientific works. The result of the research is that through these three main efforts, several important points are obtained. The knowledge stage is obtained from information from the elders. The planning stage, when the heads of RTs and residents are gathered collectively to determine the date of the event. The creativity stage, when the event is interspersed with door prize draws to attract the younger generation. Some of these efforts are made to maintain traditions that have been passed down from generation to generation so that they are not lost, and of course in this case interpersonal communication and organizational communication take an important role in the implementation of the Ruwat Bumi tradition that has survived to this day.